INPUT INFLUENCES ON AN OPTICAL-ELECTRONIC DEVICE WHEN MEASURING ANGULAR COORDINATES OF DISTANT OBJECTS: INPUT INFLUENCES ON AN OPTICAL-ELECTRONIC DEVICE WHEN MEASURING ANGULAR COORDINATES OF DISTANT OBJECTS - Getsov, Peter; Stoyanov, Stiliyan (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
An attempt for specifying the concept of input effects has been made in the article in order more data to be systematized about them, to be specified the composition and their effect over the planning and functioning of electro-optical device. An analysis has been made, showing the impact of the input effects over the functionality of the electronic-optical device for measuring the position of distant objects according to angular coordinates.